Appropriate application of pneumatic barrier for improving grinding performance. (2015) - Mandal, Bijoy; Das, Santanu; Banerjee, Simul
High grinding zone temperature is the primary reason behind several grinding defects. To control thermal defects, usually large quantity of grinding fluid is employed. However, much of applied grinding fluid is reported to be wasted because of the development of a stiff air layer surrounding the rotating wheel. In the present experimental work, an indigenously introduced setup utilising a pneumatic barrier is used for controlling the adverse effect of stiff air layer formed around the grinding wheel. Different parameters of the pneumatic barrier setup are optimised by using response surface methodology (RSM). Further, experiments are performed in surface grinding with the provision of pneumatic barrier. It is observed that applying conventional grinding fluid by providing the pneumatic barrier at optimised condition, tangential and normal force components are reduced significantly, and favourable grinding chips and good ground surface is generated in comparison with the conventionally used flood cooling.